2018
DOI: 10.1186/s12915-017-0471-6
|View full text |Cite
|
Sign up to set email alerts
|

Phthiocerol dimycocerosates promote access to the cytosol and intracellular burden of Mycobacterium tuberculosis in lymphatic endothelial cells

Abstract: BackgroundPhthiocerol dimycocerosates (PDIM), glycolipids found on the outer surface of virulent members of the Mycobacterium tuberculosis (Mtb) complex, are a major contributing factor to the pathogenesis of Mtb. Myelocytic cells, such as macrophages and dendritic cells, are the primary hosts for Mtb after infection and previous studies have shown multiple roles for PDIM in supporting Mtb in these cells. However, Mtb can infect other cell types. We previously showed that Mtb efficiently replicates in human ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
128
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(135 citation statements)
references
References 49 publications
7
128
0
Order By: Relevance
“…We next sought to understand M. tuberculosis factors that contributed to the intracellular cording phenotype in hLEC. We have previously shown that the ESX-1 secretion system, encoded in the RD1 genomic region, and the cell wall lipid phthiocerol dimycocerosate (PDIMs) are required for intracellular replication of M. tuberculosis in hLEC (Lerner et al, 2016; Lerner et al, 2018). Infection with the M. tuberculosis ΔRD1 mutant that lacks the ESX-1 secretion system was not able to form cords but instead exhibited smaller clumps of bacteria sometimes with a mesh-like appearance ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next sought to understand M. tuberculosis factors that contributed to the intracellular cording phenotype in hLEC. We have previously shown that the ESX-1 secretion system, encoded in the RD1 genomic region, and the cell wall lipid phthiocerol dimycocerosate (PDIMs) are required for intracellular replication of M. tuberculosis in hLEC (Lerner et al, 2016; Lerner et al, 2018). Infection with the M. tuberculosis ΔRD1 mutant that lacks the ESX-1 secretion system was not able to form cords but instead exhibited smaller clumps of bacteria sometimes with a mesh-like appearance ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because M. tuberculosis intracellular cords formed in the cytosol and induced a pathogen cytosolic recognition signature in hLEC associated with xenophagy (Watson et al, 2012a), we investigated whether M. tuberculosis cords were targeted by selective autophagy. In hLEC, M. tuberculosis targeting via selective autophagy is PDIM dependent (Lerner et al, 2018) and entirely RD1 dependent ( Supplementary Fig. 2 ) suggesting that in hLECs, xenophagy primarily recognises mycobacteria that access the cytosol, the intracellular location for M. tuberculosis cording.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ESX-1-mediated phagosomal permeabilization is associated with membrane damage in both M. tuberculosis and M. marinum [16,17,27,28,3032]. M. tuberculosis strains deficient in ESX-1 or PDIM synthesis show reduced galectin-3 or galectin-8 recruitment to intracellular sites of infection[23,24,33,34]. If the endosomal membrane is damaged, cytosolic galectins bind to lumenal β-galactoside-containing glycans that become exposed on damaged vesicles, and can be visualized by immunofluorescence microscopy[23,24,3336].…”
Section: Resultsmentioning
confidence: 99%
“…M. tuberculosis strains deficient in ESX-1 or PDIM synthesis show reduced galectin-3 or galectin-8 recruitment to intracellular sites of infection[23,24,33,34]. If the endosomal membrane is damaged, cytosolic galectins bind to lumenal β-galactoside-containing glycans that become exposed on damaged vesicles, and can be visualized by immunofluorescence microscopy[23,24,3336]. Differing from the role of ESX-1 in phagosomal permeabilization during M. tuberculosis and M. marinum infection, the involvement of M. marinum PDIM in this process has not been demonstrated.…”
Section: Resultsmentioning
confidence: 99%